Additive manufacture of custom radiation dosimetry phantoms: An automated method compatible with commercial polymer 3D printers. (5th December 2015) - Leary, Martin; Kron, Tomas; Keller, Cameron; Franich, Rick; Lonski, Peta; Subic, Aleksandar; Brandt, Milan
Abstract: There exist significant opportunities for the improvement of radiation therapy procedures by the development of custom dosimetry phantoms for training, quality assurance, and clinical research. Additive manufacture enables custom phantom manufacture, however there exist technical challenges, namely the lack of specialised materials to mimic radiation interaction properties of natural materials, and a lack of automated methods to reduce the manual effort required to convert medical scan data into an additive component. This work demonstrates a novel approach to overcome these challenges to enable the automated manufacture of customised radiation dosimetry phantoms using commercial ultraviolet cured printers. Graphical abstract: Highlights: Additive manufacture (AM) enables custom radiation dosimetry phantom manufacture. Novel radiological data is experimentally defined for commercial AM systems. Encapsulated support material and rigid build material are feasible radiographic contrast media. Automated methods for AM contrast detail phantom (AM-CDP) manufacture are developed. AM-CDP are manufactured with commercial UV-cured polymer jetting technologies.